Hybrid aeroacoustic approach for the efficient numerical simulation of human phonation - Schoder, Stefan; Weitz, Michael; Maurerlehner, Paul; Hauser, Alexander; Falk, Sebastian; Kniesburges, Stefan; Döllinger, Michael; Kaltenbacher, Manfred (Journal of the Acoustical Society of America, 2020)
A hybrid aeroacoustic approach was developed for the efficient numerical computation of human phonation. In the first step, an incompressible flow simulation on a three-dimensional (3 D) computational grid, which is capable of resolving all relevant turbulent scales, is performed using STARCCM+ and finite volume method. In the second step, the acoustic source terms on the flow grid are computed and a conservative interpolation to the acoustic grid is performed. Finally, the perturbed convective wave equation is solved to obtain the acoustic field in 3 D with the finite element solver CFS++. Thereby, the conservative transformation of the acoustic sources from the flow grid to the acoustic grid is a key step to allow coarse acoustic grids without reducing accuracy. For this transformation, two different interpolation strategies are compared and grid convergence is assessed. Overall, 16 simulation setups are compared. The initial (267 000 degrees of freedom) and the optimized (21 265 degrees of freedom) simulation setup were validated by measurements of a synthetic larynx model. To conclude, the total computational time of the acoustic simulation is reduced by 95% compared to the initial simulation setup without a significant reduction of accuracy, being 7%, in the frequency range of interest.
CRIS-Team Scopus Importer:2020-03-10